Atmospheres of Breathing - Škof, Lenart; Berndtson, Petri (State University of New York Press, 2018)
Attempts to think anew about philosophical questions from the perspective of breath and breathing. As a physiological or biological matter, breath is mostly considered to be mechanical and thoughtless. By expanding on the insights of many religions and therapeutic practices, which emphasize the cultivation of breath, the contributors argue that breath should be understood as fundamentally and comprehensively intertwined with human life and experience. Various dimensions of the respiratory world are referred to as "atmospheres" that encircle and connect human existence, coexistence, and the world. Drawing from a number of traditions of breathing, including from Indian and East Asian religion and philosophy, the book considers breath in relation to ontological, hermeneutical, phenomenological, ethical, and aesthetic concerns in philosophy. The wide-ranging topics include poetry, theater, environmental issues and health, feminism, and media studies.